An Experimental Study of Heat Transfer and Friction Factor Characteristics of Finned Flat Tube Banks with In-Line Tubes Configurations - Tahseen, Tahseen Ahmad; M., Ishak; M. M., Rahman (Trans Tech Publications, Switzerland, 2014)
The experimental study has been made to investigate heat transfer and pressure drop for air flow around finned flat tube banks in-line configurations with laminar forced convection. Measurements were conducted for twelve tubes in the flow direction, four tubes in the row. Four air velocity (0.2, 0.5, 0.8 and 2.0 m/s) identical to the Reynolds number, ReDh based hydraulic diameter varied 124 to 1238. The total heat flux supplies in all tubes change four times from 473.2 to 3871.7 W/m2. The study results indicate that the average heat transfer coefficient,h and the average Nusselt number. of all tubes have increased 113.6%-150.3% with ReDh numbers varying from 124 to 1238 at the fixed heat flux. Likewise, the friction factor decreases 57.7% with a ReDh number range 124-1238.